Intergovernmental Conflict in Nigeria: A Federalism Framework for Understanding Causes, Consequences, and Solutions - Yusuf, Tashok Manna; Monday, Omodia Stephen (Yayasan Ilomata, 2025)
The Nigerian intergovernmental relations system is central to the effective working of governance because it involves cooperation among federal, state, and local governments. Intergovernmental conflicts have a tendency of undermining this system, thereby its effectiveness in ensuring public services and fostering national integration minimal. Descriptive analysis is applied in this book to analyze the causes, effects, and potential solutions of intergovernmental conflict in Nigeria. The study identifies some of the key drivers that are responsible for the incidence of such conflicts, which are uncertainties in the constitution that result in conflicting mandates and disagreements, unequal resource allocation that results in competition among governments, and party politics-influenced competition for political power. Inefficient administration and entrenched corruption also sustain such tensions, given that they turn good governance and public service delivery into a fantasy. The consequences of these struggles are far-reaching, ranging from delay and below-standard services to loss of public confidence in government institutions and hindrance of socio-economic development. Furthermore, intergovernmental strife gives rise to regional disintegration, promoting challenges of national disintegration. Considering these challenges, the paper establishes several conflict management measures. These would entail constitutional amendments that would spell out the roles and responsibilities of every level of government, ensure better distribution of resources, and improve communication and coordination among the federal, state, and local governments. Of prime concern also is building the capability of government employees through training and instituting mechanisms for accountability. Lastly, the application of an impartial body to settle disputes would provide the nation with a third-party mechanism for dispute settlement where grievances would be settled. In embracing such processes, the Nigerian IGR can be simplified, resulting in improved governance, guaranteed socio-economic progress, and enhanced national unity and therefore resulting in long-term development and stability of the nation